2007
DOI: 10.1038/labinvest.3700671
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells of human colorectal cancer and healthy colon reveal phenotypic differences in culture

Abstract: Antiangiogenic drugs have been used successfully for the treatment of colorectal cancer (CRC). Viable tumor endothelial cells (TEC) and normal endothelial cells (NEC) of uninvolved colon tissue of the same patient have not been available to optimize treatment strategies in vitro. Therefore, our target was to establish a protocol for the isolation of TEC and NEC. These cells were isolated with very high purity via magnetic cell sorting of tissue samples obtained from CRC and healthy colon of eight patients. TEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…In the present study E-selectin was expressed on HCTEC after stimulation with LPS, TNF-· and IL-1ß. These results are in agreement with the observation of Schellerer et al, who found E-selectin induction in IL-1ß-stimulated tumor-derived endothelial cells from colon carcinomas (6). In both culture studies the basal E-selectin level under unstimulated conditions was negative.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study E-selectin was expressed on HCTEC after stimulation with LPS, TNF-· and IL-1ß. These results are in agreement with the observation of Schellerer et al, who found E-selectin induction in IL-1ß-stimulated tumor-derived endothelial cells from colon carcinomas (6). In both culture studies the basal E-selectin level under unstimulated conditions was negative.…”
Section: Discussionsupporting
confidence: 83%
“…These significant differences between normal and tumor endothelial cells necessitate the use of endothelial cells isolated from tumor tissue for studying the mechanisms of tumor angiogenesis and endothelium-tumor interaction. Until now limited studies were carried out using cultured tumorderived endothelial cells from carcinomas (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the cells were of endothelial blood cell origin (CD31-, CD105-, VEcadherin-positive; E-selectin-, VCAM-1-, ICAM-1-positive after stimulation with inflammatory cytokines; capability to form capillaries in matrigel, take up acetylated LDL and bind ulex europaeus; CD45-, CD68-, CK-20-, podoplanin-negative). Moreover, the isolated TECs maintained differences from NECs during long-term culture for example by decreased von Willebrand factor (vWF) levels in the isolated tumor endothelial cells as well as in the original cancer tissue biopsies compared to the corresponding normal endothelial cells and normal colon biopsy (Schellerer et al, 2007). Meanwhile, we could show that the TEC isolated from CRC differ from each other also at the transcriptome and genome level (data unpublished).…”
Section: Tumor Angiogenesis and Tumor Vesselsmentioning
confidence: 66%
“…Until recently, no viable, pure TEC cultures from human colorectal carcinomas were available, and the biological phenotype of these cells was not characterized at the functional level. We have developed the first protocol for the routine isolation of both CRC TECs and the corresponding ECs from normal colon tissue (NECs) by collagenase II-digestion followed by multiple CD31-MACS selections (Schellerer et al, 2007). It was demonstrated that the cells were of endothelial blood cell origin (CD31-, CD105-, VEcadherin-positive; E-selectin-, VCAM-1-, ICAM-1-positive after stimulation with inflammatory cytokines; capability to form capillaries in matrigel, take up acetylated LDL and bind ulex europaeus; CD45-, CD68-, CK-20-, podoplanin-negative).…”
Section: Tumor Angiogenesis and Tumor Vesselsmentioning
confidence: 99%
“…According to our published protocol (34), small pieces from the non-necrotic center of the CRC as well as from the healthy tissue at a minimum distance of 10 cm from the visible tumor margin were used for the generation of a single-cell suspension (34). Approximately 5 to 7 days after initial seeding, endothelial cells were removed by magnetic cell separation.…”
Section: Methodsmentioning
confidence: 99%